(untitled) (Kobe, 1930)
This book introduce about patent law, utility model law, disign law, trade-mark law, law concerning patent attorneys, sundry regulations.
Keywords: Patent laws and legislation,Trademarks,Luật pháp và luật bằng sáng chế,Nhãn hiệu hàng hoá; Japan,Japan,Nhật Bản,Nhật Bản